2014
DOI: 10.1002/2014jb011037
|View full text |Cite
|
Sign up to set email alerts
|

Changes in mining‐induced seismicity before and after the 2007 Crandall Canyon Mine collapse

Abstract: On 6 August 2007, the Crandall Canyon Mine in central Utah experienced a major collapse that was recorded as an M w 4.1 seismic event. Application of waveform cross-correlation detection techniques to data recorded at permanent seismic stations located within~30 km of the mine has resulted in the discovery of 1494 previously unknown microseismic events related to the collapse. These events occurred between 26 July 2007 and 19 August 2007 and were detected with a magnitude threshold of completeness of 0.0, abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Our results of b-values of these seismic events are comparable with previous studies for the Utah mining region (Smith et al 1974;Pechmann et al 2008;Kubacki et al 2014). These calculations, however, were completed over two years or less.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results of b-values of these seismic events are comparable with previous studies for the Utah mining region (Smith et al 1974;Pechmann et al 2008;Kubacki et al 2014). These calculations, however, were completed over two years or less.…”
Section: Discussionsupporting
confidence: 90%
“…Mining induced seismicity (MIS) in central Utah has been monitored by the University of Utah Seismograph Station (UUSS) regional network since 1978 (Kubacki et al . ). The MIS is mostly a result of underground mine collapse and shear‐slip motion on rock fractures (Pechmann et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…From October 2000 to April 2001, an array of 12 seismometers was installed over the Trail Mountain Mine and used to locate approximately 1900 seismic events coincident with longwall mining operations [Arabasz et al, 2005;Boltz et al, 2014]. Following the 6 August 2007 Crandall Canyon mine collapse, five seismometers were temporarily installed above and next to the mine, resulting in~1000 well-located aftershocks after application of waveform cross-correlation techniques [Kubacki et al, 2014]. These and other studies have shown that MIS in Utah occurs very close to mine level, at depths of < 2 km below the surface.…”
Section: L -M C As a Depth Discriminantmentioning
confidence: 99%
“…An alternative way to improve detection of small earthquakes involves waveform correlation or matched filter techniques [Kubacki et al, 2014;Zhao and Peng, 2009;Shelly et al, 2007;Shelly et al, 2013;van der Elst et al, 2013]. These methods have proven to be highly effective in recovering events, often below the noise level, where a larger event has already occurred.…”
Section: Introductionmentioning
confidence: 99%